IMPORTANCE OF MEDIA EDUCATION FOR YOUNG PEOPLE IN THE FIELD OF FOOD BIOTECHNOLOGY - O. N. Goryacheva; S. A. Goryacheva (Вестник университета)
Influence of the media on the market of biotechnological products has been studied. Awareness of citizens about food technologies and genetically modified foods has been analysed. Position of state institutions and the scientific community regarding genetic engineering, broadcast through the media, indirectly affects the attitude of young people to genetically modified foods. The results of a sociological survey of young people and an analysis of media materials have revealed the importance of media resources in shaping public opinion. The study has clarified that among young people the attitude to genetically modified foods is largely determined by expert assessments of public people and advertising that creates the image of the product. The relevance of the issue lies in understanding the importance of informing the population in matters of biotechnology in general and media education of the youth audience in particular. The conducted study on the attitude of young people to genetically modified products and food bioengineering has assisted in revealing the importance of the issue raised by the authors and allowed them to formulate recommendations on providing a comprehensive program to increase youth media literacy in food biotechnology. The proposals aimed at providing a comprehensive program for improving media literacy are related to the search for ways to increase the level of public confidence in genetically modified foods.